2020
DOI: 10.3390/catal10111267
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the Performance of Nano-Ni Catalysts by Palladium Doping in Flow Hydrogenation of Sulcatone

Abstract: The effect of Pd doping on nano-Ni catalyst hydrogenation aptitude in sulcatone (6-methyl-5-hepten-2-one) hydrogenation was investigated. Obtained results demonstrated that the addition of non-catalytic amounts of Pd to the surface of parent Ni catalyst improves the activity to the extent that it surpassed the activity of 2.16 wt% Pd catalyst (model catalyst) at optimal reaction conditions in the flow hydrogenation of an unsaturated ketone. Pd doping improves hydrogen activation on the catalyst, which was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Sá and co-workers investigated the effect of palladium doping on a nano-nickel catalyst during the hydrogenation of sulcatone under continuous-flow conditions [8]. The authors observed that doping enhanced hydrogen activation on the catalyst, which was found to be a rate-limiting step using kinetic isotopic measurements and theoretical calculations.…”
mentioning
confidence: 99%
“…Sá and co-workers investigated the effect of palladium doping on a nano-nickel catalyst during the hydrogenation of sulcatone under continuous-flow conditions [8]. The authors observed that doping enhanced hydrogen activation on the catalyst, which was found to be a rate-limiting step using kinetic isotopic measurements and theoretical calculations.…”
mentioning
confidence: 99%